The effect of magnetic ions and disorder on superconducting beta ''-(BEDT-TTF)(4)[(H3O)M(C2O4)(3)]center dot C6H5NO2 salts, where M = Ga and Cr - Bangura, A; Coldea, A; Ardavan, A; Singleton, J; Akutsu-Sato, A; Akatsu, H; Day, P (2004)
We report in magnetotransport measurements performed in magnetic fields of up to 33 T and at low temperatures (0.45 K